A method for preparing a high-density pick

By using laser cladding technology of metal-based composite powder, rare earth modified deteriorant powder and magnesium powder on the surface of the cutter, the problem of easy scaling and pore formation of the cutter material during the working process is solved, and the effect of improving density and mechanical properties is achieved.

CN119465142BActive Publication Date: 2025-04-08山东艾德实业有限公司

Patent Information

Application Number
CN202510053498.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing tooth cutting materials are prone to fracture or breaking due to friction, extrusion and impact during the working process, and pores are easily formed during the plating process, reducing density.

Method used

The metal-based composite powder is mixed with rare earth modification agent powder and magnesium powder, and a cladding protective layer is prepared on the surface of the cut teeth through high-temperature laser cladding technology to improve the density and mechanical properties of the material.

Benefits of technology

It has achieved improvement of the density, hardness and wear resistance of the teeth cutter, enhanced impact resistance and corrosion resistance, and extended the service life of the teeth cutter.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-density pick, and belongs to the technical field of surface treatment of alloy materials. The preparation method comprises the following steps: after treating the surface of the pick substrate with a shot blasting machine, ultrasonic cleaning and drying are performed in sequence to obtain a pre-treated pick substrate; the pre-treated pick substrate is placed on a workbench of a laser cladding device, and metal-based composite powder, rare earth modified modifier powder and magnesium powder are mixed and put into a powder feeder, and then argon is used as a powder feeding gas to perform laser cladding on the pre-treated pick substrate; after the laser cladding is completed, the pre-treated pick substrate obtained by cladding is subjected to heat preservation annealing to obtain the high-density pick. The present invention uses a metal-based composite powder as a cladding substrate, which is mixed with rare earth modified modifier powder and magnesium powder and then subjected to high-temperature laser cladding to obtain a pick with high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment of alloy materials, and in particular relates to a method for preparing a high-density pick. Background Art

[0002] The pick is a common engineering machinery device, widely used in engineering machinery such as excavators and loaders. Its main function is to scrape off soil or rock through a rotating cutter during excavation operations to achieve the purpose of earth excavation or stone crushing. At present, my country mostly uses coal mining machines or tunneling machines to mine coal minerals. Generally, the pick is installed on its cutting head to cut coal seams or rocks. Pick mining is a cyclical working process, including two halves: continuous coal mining and idling. During the coal mining process, the pick cuts and crushes the coal seam under the action of strong thrust, and produces intense friction and extrusion between the pick and the coal seam, causing the temperature of the pick head to rise sharply. When the coal seam structure is more complex, there are more interlayers of gangue inside the coal seam. The hardness of the interlayers of gangue is usually relatively high, which will produce huge impact pressure on the pick head, causing the cemented carbide to break or even break. During the operation of the pick, the tooth head is subjected to the combined effects of multiple factors such as periodic impact of the coal seam, severe friction, extrusion, violent impact of the gangue, and alternating thermal stress inside the alloy. Therefore, the tooth head is required to have high hardness, high wear resistance and other properties. The forms of pick failure include wear, chipping and alloy fracture, among which wear failure is the main form of pick failure. The improvement directions of picks in the prior art include improvements in the composition of alloy raw materials and surface coatings. The improvement of alloy composition raw materials is mainly to reduce the generation of pores by using alloy materials with low porosity, thereby improving the strength and wear resistance of the pick; the surface coating improvement is to plate an alloy metal protective layer on the surface of the pick substrate, thereby improving the strength and wear resistance of the pick.

[0003] The patent application with the publication number CN116855937A discloses a pick and a method for preparing the pick by laser cladding. The invention laser-clads a layer of low-hardness iron-based transition coating on the surface of the pick substrate to reduce the residual stress concentration caused by the difference in thermal expansion coefficient between the nickel-based alloy and tungsten carbide composite coating and the substrate after heating. The iron-based transition coating 316L stainless steel is a non-magnetic stainless steel material, and there is no spark phenomenon during grinding, which meets the safety requirements of mining machinery. At the same time, the invention cooperates with the heat preservation and slow cooling process after laser cladding to slowly release the residual stress generated in the laser cladding process, avoid excessive concentration of residual stress and cracking of the cladding layer, and obtain a complete laser cladding strengthening coating without crack defects. The cladding layer has a high bonding strength with the pick substrate and has the advantages of high hardness and strong wear resistance.

[0004] The patent application with publication number CN113774377A discloses a plasma cladding welding coating formula and process for improving the wear resistance of cutting teeth. The invention mixes powdered Al2O3, MoSi2 and Mo in a ratio of 25~35 parts: 25~35 parts: 30~50 parts, and optimizes the powder ratio and spraying process of the plasma cladding welding coating to improve the uniformity of the dispersion distribution of ceramic phases such as Al2O3 and MoSi2, thereby achieving improved wear resistance and impact resistance of the cutting teeth.

[0005] Although the above improvements have a certain effect on improving the wear resistance and impact resistance of the pick, the protective gas used in the coating process is easily captured in the cladding layer. The metal surface tension in the cladding layer is high, the fluidity is poor, and the gas is difficult to discharge, which in turn forms pores and reduces the density of the pick. Highly dense materials usually have better physical and chemical properties, which can significantly improve the wear resistance, strength and corrosion resistance of the pick. Specifically, the effect of density on the pick is mainly reflected in the following aspects: (1) Reducing porosity: Highly dense materials have low porosity, which can effectively reduce the internal weaknesses of the material, thereby improving the overall strength and wear resistance; (2) Improving impact resistance: The higher the density of the material, the tighter its internal structure, which can better absorb and disperse external impact forces and reduce the risk of fracture; (3) Enhancing corrosion resistance: Dense materials are not easily corroded by chemical substances and can maintain stable performance in harsh environments.

[0006] Therefore, it is of great significance to improve the strength, wear resistance and tensile strength of the pick by treating the density of the cladding layer coated on the surface of the pick. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention uses metal-based composite powder as the cladding substrate, mixes it with rare earth modified modifier powder and magnesium powder, and then undergoes high-temperature laser cladding to obtain a pick with high density, thereby solving the technical problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents:

[0008] A method for preparing a high-density pick, the method comprising the following steps:

[0009] After the surface of the pick base plate is treated by a shot blasting machine, ultrasonic cleaning and drying are performed in sequence to obtain a pre-treated pick base plate;

[0010] The pre-treated pick substrate is placed on a workbench of a laser cladding device, a metal-based composite powder, a rare earth modified modifier powder and a magnesium powder are mixed and put into a powder feeder, and then argon gas is used as a powder feeding gas to perform laser cladding on the pre-treated pick substrate;

[0011] After the laser cladding is completed, the pre-treated pick substrate obtained by cladding is subjected to heat preservation annealing to obtain the high-density pick.

[0012] Furthermore, the pick base plate is made of 30CrMnSi steel or 35CrMnSi steel.

[0013] Preferably, the pick base plate is made of 35CrMnSi steel.

[0014] Furthermore, the method for preparing the metal-based composite powder comprises the following steps:

[0015] Titanium carbide and tungsten carbide are mixed in a weight ratio of 1:1-3 and placed in a ball mill, the material-to-ball ratio is controlled to be 4-5:1, and then ball milled at a speed of 300r / min-400r / min for 2h-3h and dried to obtain the metal-based composite powder.

[0016] Furthermore, the preparation method of the rare earth modified modifier powder comprises the following steps:

[0017] The iron-aluminum alloy and the rare earth ferrosilicon alloy are mixed and smelted in a temperature environment of 1400°C to 1500°C for 20min to 30min to obtain a mixed melt and the mixture is kept warm. An aluminum-copper alloy is added to the kept mixed melt and mixed and stirred for 5min to 10min. The mixture is then cooled to 700°C to 800°C and subjected to a modification treatment for 30min to 40min to obtain a rare earth modified modifier powder.

[0018] Furthermore, the mass ratio of iron to aluminum in the iron-aluminum alloy is 80:20.

[0019] Furthermore, the rare earth content in the rare earth ferrosilicon alloy is 28% to 29%.

[0020] Furthermore, the mass ratio of aluminum to copper in the aluminum-copper alloy is 20:80.

[0021] Furthermore, the weight ratio of the iron-aluminum alloy: the rare earth ferrosilicon alloy: the aluminum-copper alloy is 3-5:1-2:1.

[0022] Furthermore, the weight ratio of the metal-based composite powder: the rare earth modified modifier powder: the magnesium powder is 95-96.2: 3-3.8: 0.8-1.2.

[0023] Furthermore, the conditions for laser cladding of the pre-treated pick substrate include laser power of 3000W~3500W, laser spot diameter of 3mm~4mm, powder feeding speed of 10g / min~12g / min, scanning speed of 200mm / min~220mm / min and overlap rate of 35%~40%.

[0024] Furthermore, the heat preservation annealing conditions include treatment at 300° C. to 400° C. for 2 h to 3 h.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention adopts tungsten carbide and titanium carbide with high strength and high wear resistance as the main matrix material of the cladding protective layer on the surface of the pick. First, the iron-aluminum alloy and the rare earth ferrosilicon alloy are mixed and smelted, and then the aluminum-copper alloy is added to prepare the rare earth modified modifier. The introduction of aluminum, copper and silicon can enhance the mechanical properties of the cladding layer through the solid solution strengthening mechanism. Rare earth can promote grain refinement, and grain refinement helps to reduce pores and reduce the surface tension of the phase interface. However, when rare earth oxides are used, due to the high melting point, aluminum will be overburned. Therefore, rare earth is introduced into the modifier by the method of rare earth ferrosilicon alloy, thereby obtaining the advantages of rare earth. After iron is alloyed with aluminum, copper, rare earth, etc., it can not only improve the strength, but also improve the toughness of the cladding protective layer. A small amount of magnesium powder can reduce the surface tension of the metal melt. By cooperating with rare earth, when the cladding protective layer is prepared on the surface of the pick by high-temperature laser cladding, the fluidity of the melt can be improved, and the melt can better infiltrate into the pick material. Refined grains can withstand greater deformation, making the material more tough, and small-sized grains have the effect of hindering crack expansion, so that when the material is dislocated, it needs to overcome greater resistance, thereby improving the strength of the cladding layer. The reduction in the surface tension of the melt is conducive to better flow of the melt during the smelting process, thereby discharging the gas. Through the coordinated cooperation of refining grains and reducing the surface tension of the melt, the density of the cladding protective layer on the surface of the pick is improved, and the mechanical properties of the pick are improved. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0029] Preparation Example 1:

[0030] The preparation of metal-based composite powder specifically includes the following processes:

[0031] Titanium carbide powder and tungsten carbide powder were mixed in a planetary ball mill at a weight ratio of 1:1, and 5 mm stainless steel balls were used as ball milling media. The ball-to-material ratio was controlled to be 4:1, and then the ball milling was performed at a speed of 300 r / min for 2 hours. After the ball milling, the ball mill was rinsed with alcohol to obtain a mixed liquid containing abrasives, and the mixed liquid was heated and dried in an electric furnace to constant weight to obtain a metal-based composite powder.

[0032] Preparation Example 2:

[0033] The preparation of metal-based composite powder specifically includes the following processes:

[0034] Titanium carbide powder and tungsten carbide powder were mixed in a planetary ball mill at a weight ratio of 1:2, and 5 mm stainless steel balls were used as ball milling media. The ball-to-material ratio was controlled to be 4.5:1, and then the ball milling was performed at a speed of 350 r / min for 2.5 hours. After the ball milling, the ball mill was rinsed with alcohol to obtain a mixed liquid containing abrasives, and the mixed liquid was heated and dried in an electric furnace to constant weight to obtain a metal-based composite powder.

[0035] Preparation Example 3:

[0036] The preparation of metal-based composite powder specifically includes the following processes:

[0037] Titanium carbide powder and tungsten carbide powder were mixed in a planetary ball mill at a weight ratio of 1:3, and 5 mm stainless steel balls were used as ball milling media. The ball-to-material ratio was controlled to be 5:1, and then the ball milling was performed at a speed of 400 r / min for 3 hours. After the ball milling, the ball mill was rinsed with alcohol to obtain a mixed liquid containing abrasives, and the mixed liquid was heated and dried in an electric furnace to constant weight to obtain a metal-based composite powder.

[0038] Preparation Example 4:

[0039] The preparation of metal-based composite powder specifically includes the following processes:

[0040] Titanium carbide powder and tungsten carbide powder were mixed in a planetary ball mill at a weight ratio of 1:3, and 5 mm stainless steel balls were used as ball milling media. The ball-to-material ratio was controlled to be 5:1, and then the ball milling was performed at a speed of 500 r / min for 4 hours. After the ball milling, the ball mill was rinsed with alcohol to obtain a mixed liquid containing abrasives, and the mixed liquid was heated and dried in an electric furnace to constant weight to obtain a metal-based composite powder.

[0041] Preparation Example 5:

[0042] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0043] Weigh 3 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and 1 part by weight of rare earth ferrosilicon alloy (rare earth content 28%), mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 200°C and dry to constant weight, then put it into a graphite crucible and heat it to 1400°C and stir and react for 20 minutes to obtain a mixed melt and keep it at 1400°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 20:80), then quickly add it to the mixed melt and stir and react for 5 minutes, then cool it to 700°C for modification for 30 minutes, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0044] Preparation Example 6:

[0045] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0046] Weigh 4 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and 1.5 parts by weight of rare earth ferrosilicon alloy (rare earth content 28%), mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 250°C and dry to constant weight, then put it into a graphite crucible and heat it to 1450°C and stir and react for 25 minutes to obtain a mixed melt and keep it at 1450°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 20:80), then quickly add it to the mixed melt and stir and react for 7 minutes, then cool it to 750°C for modification for 35 minutes, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0047] Preparation Example 7:

[0048] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0049] Weigh 5 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and 2 parts by weight of rare earth ferrosilicon alloy (rare earth content 29%), mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 300°C and dry to constant weight, then put it into a graphite crucible and heat it to 1500°C and stir and react for 30 minutes to obtain a mixed melt and keep it at 1500°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 20:80), then quickly add it to the mixed melt and stir and react for 10 minutes, then cool it to 800°C for modification for 40 minutes, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0050] Preparation Example 8:

[0051] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0052] Weigh 5 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and 5 parts by weight of rare earth ferrosilicon alloy (rare earth content 33%), mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 300°C and dry to constant weight, then put it into a graphite crucible and heat it to 1500°C and stir and react for 30 minutes to obtain a mixed melt and keep it at 1500°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 20:80), then quickly add it to the mixed melt and stir and react for 10 minutes, then cool it to 800°C for modification for 40 minutes, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0053] Preparation Example 9:

[0054] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0055] Weigh 5 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 20:80) and 2 parts by weight of rare earth ferrosilicon alloy (rare earth content 29%), mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 300°C and dry to constant weight, then put it into a graphite crucible and heat it to 1500°C and stir and react for 30 minutes to obtain a mixed melt and keep it at 1500°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 50:50), then quickly add it to the mixed melt and stir and react for 10 minutes, then cool it to 800°C for 40 minutes of modification, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0056] Preparation Example 10:

[0057] The preparation of rare earth modified modifier powder specifically includes the following processes:

[0058] Weigh 5 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and 2 parts by weight of lanthanum oxide, mix and crush through a 50-mesh sieve to obtain a mixed metal powder. Heat the mixed metal powder to 300°C and dry to constant weight, then put it into a graphite crucible and heat it to 1500°C and stir and react for 30 minutes to obtain a mixed melt and keep it at 1500°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 50:50), then quickly add it to the mixed melt and stir and react for 10 minutes, then cool it to 800°C for 40 minutes of modification, then cool and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0059] Preparation Example 11:

[0060] The preparation of modified modifier powder specifically includes the following processes:

[0061] Weigh 5 parts by weight of iron-aluminum alloy (iron-aluminum mass ratio of 80:20) and crush it through a 50-mesh sieve to obtain metal powder. Heat the metal powder to 300°C and dry it to constant weight, then put it into a graphite crucible and heat it to 1500°C and stir it for 30 minutes to obtain a melt and keep it at 1500°C. Melt 1 part by weight of aluminum-copper alloy (aluminum-copper mass ratio of 20:80), then quickly add it to the melt and stir it for 10 minutes, then cool it to 800°C for 40 minutes of modification, then cool it and crush it through a 200-mesh sieve to obtain a rare earth modified modifier powder.

[0062] Example 1: Preparation of a high-density pick, specifically including the following process:

[0063] The pick base plate made of 30CrMnSi steel was polished with a shot blasting machine to remove the surface oxide layer and oil, and then placed in an acetone solution and cleaned at an ultrasonic power of 300W for 5 minutes. After cleaning, it was dried to constant weight to obtain a pre-treated pick base plate. The pre-treated pick base plate was placed on the workbench of the laser cladding equipment, 95 parts by weight of the metal-based composite powder obtained in Preparation Example 1, 3.8 parts by weight of the rare earth modified modifier powder obtained in Preparation Example 5, and 1.2 parts by weight of magnesium powder were weighed and mixed evenly and placed in a powder feeder, and then the pre-treated pick base plate was melted with a laser power of 3000W, the laser spot diameter was adjusted to 3mm, and then argon was used as the powder feeding gas, the powder feeding speed was controlled to 10g / min, and the laser melted area was sprayed with powder, the scanning speed was controlled to 200mm / min, and the overlap rate was controlled to 35%, until the laser cladding of the surface of the pre-treated pick base plate was completed, and then it was kept at 300℃ for 2h, and then naturally cooled to room temperature to obtain a high-density pick.

[0064] Example 2: Preparation of a high-density pick, specifically including the following process:

[0065] The pick base plate made of 30CrMnSi steel was polished with a shot blasting machine to remove the surface oxide layer and oil stains, and then placed in an acetone solution for cleaning at an ultrasonic power of 300 W for 10 minutes. After cleaning, it was dried to constant weight to obtain a pretreated pick base plate. The pretreated pick substrate is placed on the workbench of the laser cladding equipment, 95.5 parts by weight of the metal-based composite powder obtained in Preparation Example 2, 3.5 parts by weight of the rare earth modified agent powder obtained in Preparation Example 6 and 1 part by weight of magnesium powder are weighed, mixed evenly and put into a powder feeder, and then the pretreated pick substrate is melted with a laser power of 3300 W, the laser spot diameter is adjusted to 3.5 mm, and then argon is used as the powder feeding gas, the powder feeding speed is controlled to 11 g / min, and the laser melted area is sprayed with powder, the scanning speed is controlled to 210 mm / min, and the overlap rate is controlled to 37% until the laser cladding of the surface of the pretreated pick substrate is completed, and then it is heat-treated at 350°C for 2.5 hours, and then naturally cooled to room temperature to obtain a high-density pick.

[0066] Example 3: Preparation of a high-density pick, specifically including the following process:

[0067] The pick base plate made of 30CrMnSi steel was polished with a shot blasting machine to remove the surface oxide layer and oil, and then placed in an acetone solution and cleaned at an ultrasonic power of 300W for 15min. After cleaning, it was dried to constant weight to obtain a pre-treated pick base plate. The pre-treated pick base plate was placed on the workbench of the laser cladding equipment, 96.2 parts by weight of the metal-based composite powder obtained in Preparation Example 3, 3 parts by weight of the rare earth modified modifier powder obtained in Preparation Example 7, and 0.8 parts by weight of magnesium powder were weighed and mixed evenly and placed in a powder feeder, and then the pre-treated pick base plate was melted with a laser power of 3500W, the laser spot diameter was adjusted to 4mm, and then argon was used as the powder feeding gas, the powder feeding speed was controlled to 12g / min, and the laser melted area was sprayed with powder, the scanning speed was controlled to 220mm / min, and the overlap rate was controlled to 40%, until the laser cladding of the surface of the pre-treated pick base plate was completed, and then the heat treatment was carried out at 400℃ for 3h, and then naturally cooled to room temperature to obtain a high-density pick.

[0068] Example 4: Preparation of a high-density pick, specifically including the following process:

[0069] The pick base plate made of 35CrMnSi steel was polished with a shot blasting machine to remove the surface oxide layer and oil, and then placed in an acetone solution and cleaned at an ultrasonic power of 300W for 15min. After cleaning, it was dried to constant weight to obtain a pre-treated pick base plate. The pre-treated pick base plate was placed on the workbench of the laser cladding equipment, 96.2 parts by weight of the metal-based composite powder obtained in Preparation Example 3, 3 parts by weight of the rare earth modified modifier powder obtained in Preparation Example 7, and 0.8 parts by weight of magnesium powder were weighed and mixed evenly and placed in a powder feeder, and then the pre-treated pick base plate was melted with a laser power of 3500W, the laser spot diameter was adjusted to 4mm, and then argon was used as the powder feeding gas, the powder feeding speed was controlled to 12g / min, and the laser melted area was sprayed with powder, the scanning speed was controlled to 220mm / min, and the overlap rate was controlled to 40%, until the laser cladding of the surface of the pre-treated pick base plate was completed, and then the heat treatment was carried out at 400℃ for 3h, and then naturally cooled to room temperature to obtain a high-density pick.

[0070] Comparative Example 1:

[0071] A preparation method of a high-density pick includes the following steps:

[0072] The metal-based composite powder in Example 4 was replaced by the metal-based composite powder obtained in Preparation Example 4, and the other conditions remained the same as in Example 4.

[0073] Comparative Example 2:

[0074] A preparation method of a high-density pick includes the following steps:

[0075] The rare earth modified modifier powder in Example 4 was replaced by the rare earth modified modifier powder obtained in Preparation Example 8, and the other conditions were the same as those in Example 4.

[0076] Comparative Example 3:

[0077] A preparation method of a high-density pick includes the following steps:

[0078] The rare earth modified modifier powder in Example 4 was replaced by the rare earth modified modifier powder obtained in Preparation Example 9, and the other conditions were the same as those in Example 4.

[0079] Comparative Example 4:

[0080] A preparation method of a high-density pick includes the following steps:

[0081] The rare earth modified modifier powder in Example 4 was replaced by the rare earth modified modifier powder obtained in Preparation Example 10, and the other conditions were the same as those in Example 4.

[0082] Comparative Example 5:

[0083] A preparation method of a high-density pick includes the following steps:

[0084] The rare earth modified modifier powder in Example 4 was replaced by the modified modifier powder obtained in Preparation Example 11, and the other conditions were the same as those in Example 4.

[0085] Comparative Example 6:

[0086] A preparation method of a high-density pick includes the following steps:

[0087] The pick base plate made of 35CrMnSi steel in Example 4 was replaced with a pick base plate made of 42CrMnMo steel, and the other conditions remained the same as in Example 4.

[0088] Comparative Example 7:

[0089] A preparation method of a high-density pick includes the following steps:

[0090] The magnesium powder in Example 4 was further increased to 2 parts by weight, and the other conditions remained the same as in Example 4.

[0091] The density of the high-density picks obtained in Examples 1 to 4 and Comparative Examples 1 to 7 was measured according to the Archimedes drainage method, and then compared with the theoretical density, the density of the high-density picks obtained in Examples 1 to 4 and Comparative Examples 1 to 7 was calculated, and the results are shown in Table 1 below.

[0092] Table 1 Density

[0093] Sources Density (%) Example 1 88.5 Example 2 90.2 Example 3 93.3 Example 4 94.1 Comparative Example 1 63.1 Comparative Example 2 65.8 Comparative Example 3 62.6 Comparative Example 4 59.7 Comparative Example 5 73.9 Comparative Example 6 81.5 Comparative Example 7 68.1

[0094] The high-density picks obtained in Examples 1 to 4 and Comparative Examples 1 to 7 were hardness tested using a Brinell hardness tester. The main test parameters were: load of 300 g, loading time of 10 s, and unloading time of 5 s. The measurement results are shown in Table 2 below.

[0095] Table 2 Hardness value

[0096] Sources Hardness value (HB) Example 1 507.8 Example 2 572.5 Example 3 629.4 Example 4 642.1 Comparative Example 1 334.7 Comparative Example 2 347.1 Comparative Example 3 329.6 Comparative Example 4 301.3 Comparative Example 5 371.4 Comparative Example 6 394.6 Comparative Example 7 362.9

[0097] The tensile strength of the high-density picks obtained in Examples 1 to 4 and Comparative Examples 1 to 7 was measured using a universal tensile testing machine at a tensile speed of 1 mm / min. The results are shown in Table 3 below.

[0098] Table 3 Tensile strength values

[0099] Sources Tensile strength (MPa) Example 1 681.9 Example 2 703.3 Example 3 719.8 Example 4 725.2 Comparative Example 1 449.2 Comparative Example 2 461.3 Comparative Example 3 444.7 Comparative Example 4 416.9 Comparative Example 5 472.7 Comparative Example 6 496.8 Comparative Example 7 465.1

[0100] The volume wear of the high-density picks obtained in Examples 1 to 4 and Comparative Examples 1 to 7 was calculated and tested using a CEF-1 multifunctional material surface performance tester. The friction mode was reciprocating dry friction, the reciprocating frequency was 1000 times / min, the applied normal force was 60N, the reciprocating length was 5mm, and the friction time was 30min. The results are shown in Table 4 below.

[0101] Table 4 Volumetric wear

[0102] Sources <![CDATA[Volume wear amount (mm 3 )]]> Example 1 0.19 Example 2 0.17 Example 3 0.13 Example 4 0.12 Comparative Example 1 0.23 Comparative Example 2 0.21 Comparative Example 3 0.24 Comparative Example 4 0.27 Comparative Example 5 0.19 Comparative Example 6 0.18 Comparative Example 7 0.21

[0103] The following conclusions can be drawn from the test results in Tables 1 to 4 above:

[0104] (1) The present invention uses metal-based composite powder as the cladding substrate, mixes it with rare earth modified agent powder and magnesium powder, and then undergoes high-temperature laser cladding to obtain high-density picks of Examples 1 to 4 having good density and mechanical properties, indicating that the preparation conditions of the present invention have a promoting effect on improving the performance of the picks.

[0105] (2) It can be found from Comparative Example 1 that due to the excessively high ball milling speed and the long ball milling time, the particle size of the obtained metal-based composite powder is too fine. The excessively fine powder has a high specific surface area and is prone to agglomeration, resulting in poor fluidity and uneven powder feeding. Under the laser cladding conditions of the present invention, the adhesion of the cladding protective layer may decrease and more pores may be generated, thereby affecting the performance of the pick.

[0106] (3) It can be found from Comparative Example 2 that although rare earth has the effect of improving melt fluidity and refining grains, when the rare earth concentration and dosage are further increased under the preparation conditions of the present invention, excessive rare earth elements may cause the melt fluidity to deteriorate, the viscosity to increase, and the brittleness of the prepared cladding protective layer to increase, which will make the material more likely to break or crack when subjected to stress.

[0107] (4) It can be found from Comparative Example 3 that when the aluminum content in the iron-aluminum alloy and the aluminum-copper alloy is increased, although aluminum can improve the mechanical properties of the cladding protective layer on the surface of the pick through the solid solution strengthening mechanism, aluminum will be overburned in a high temperature environment, resulting in poor bonding between the cladding layer and the surface of the pick, which is not conducive to the improvement of the mechanical properties of the pick.

[0108] (5) It can be found from Comparative Example 4 that although the rare earth oxide lanthanum oxide also has the effect of promoting the refinement of gold grains, the melting point of rare earth oxide is much higher than that of rare earth ferrosilicon alloy. Under the preparation conditions of the present invention, it is difficult for rare earth to be mixed into the modifier through smelting, resulting in the rare earth being difficult to play a densifying role in the protective layer cladding on the surface of the pick. If the smelting temperature is further increased, although the rare earth can be smelted, the excessively high smelting temperature is likely to cause overburning of aluminum, which is not conducive to enhancing the mechanical properties of the pick.

[0109] (6) It can be found from Comparative Example 5 that the modified modifier prepared without using rare earth ferrosilicon alloy can improve the density of the pick to a certain extent, but the effect is poor and the mechanical properties are poor.

[0110] (7) It can be found from Comparative Example 6 that when the metal-based composite powder and rare earth modified modifier powder constructed by the present invention are used for laser cladding treatment of picks, the composition of the pick material has a certain specificity and cannot be applied to all types of pick substrates.

[0111] (8) It can be found from Comparative Example 7 that although magnesium powder can reduce the surface tension of the melt, improve the wettability with the pick substrate, and thus improve the density, in the system of the present invention, excessive use may cause the resulting oxide film to be too much and too thick, which in turn inhibits the fluidity of the melt and is not conducive to the improvement of the mechanical properties of the pick.

[0112] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a high-density pick, characterized in that: The preparation method comprises the following steps: After the surface of the pick base plate is treated by a shot blasting machine, ultrasonic cleaning and drying are performed in sequence to obtain a pre-treated pick base plate; The pre-treated pick substrate is placed on a workbench of a laser cladding device, a metal-based composite powder, a rare earth modified modifier powder and a magnesium powder are mixed and put into a powder feeder, and then argon gas is used as a powder feeding gas to perform laser cladding on the pre-treated pick substrate; After the laser cladding is completed, the pre-treated pick substrate obtained by cladding is subjected to heat preservation annealing to obtain the high-density pick; The pick base plate is made of 30CrMnSi steel or 35CrMnSi steel; The preparation method of the rare earth modified modifier powder comprises the following steps: The iron-aluminum alloy and the rare earth ferrosilicon alloy are mixed and smelted in a temperature environment of 1400° C. to 1500° C. for 20 min to 30 min to obtain a mixed melt and the mixture is kept warm. The aluminum-copper alloy is added to the kept mixed melt and mixed and stirred for 5 min to 10 min. The mixture is then cooled to 700° C. to 800° C. and subjected to a modification treatment for 30 min to 40 min to obtain a rare earth modified modifier powder. The mass ratio of iron to aluminum in the iron-aluminum alloy is 80:20; The rare earth content in the rare earth ferrosilicon alloy is 28% to 29%; The mass ratio of aluminum to copper in the aluminum-copper alloy is 20:80; The weight ratio of the iron-aluminum alloy: the rare earth ferrosilicon alloy: the aluminum-copper alloy is 3-5:1-2:1; The method for preparing the metal-based composite powder comprises the following steps: Titanium carbide and tungsten carbide are mixed in a ball mill at a weight ratio of 1:1-3, and the material-ball ratio is controlled to be 4-5:1, and then ball milled at a speed of 300 r / min-400 r / min for 2h-3h and then dried to obtain the metal-based composite powder; The weight ratio of the metal-based composite powder: the rare earth modified modifier powder: the magnesium powder is 95-96.2: 3-3.8: 0.8-1.

2.

2. A method for preparing a high-density pick according to claim 1, characterized in that: The conditions for laser cladding of the pre-treated pick substrate include laser power of 3000W~3500W, laser spot diameter of 3mm~4mm, powder feeding speed of 10g / min~12g / min, scanning speed of 200mm / min~220mm / min and overlap rate of 35%~40%.

Citation Information

Patent Citations

  • Plasma cladding welding coating formula and process for improving wear resistance of cutting pick

    CN113774377A

  • Cutting pick and method for preparing cutting pick through laser cladding

    CN116855937A

  • Laser cladding nickel-aluminum-based wear-resistant coating and preparation method thereof

    CN117286493A

  • High-wear-resistance and high-anti-pinch wire drawing hub ring

    CN118497529A

Cited By

  • High-strength alloy composite cutting pick suitable for super-hard rock mining

    CN120626158A